1981
DOI: 10.1021/jm00143a001
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoid sweeteners. Synthesis and sensory evaluation of stevioside analogs nondegradable to steviol

Abstract: A new series of methylase inhibitors has been designed in which the nucleophilic methyl acceptor is attached to the adenosine and/or homocysteine fragments of the methyl donor, S-adenosyhnethionine, to form a "multisubstrate adduct". In the present case, catecholamine analogues attached through a phenethyl sulfide linkage to 5'-thioadenosine or homocysteine have been synthesized, together with the corresponding methylsulfonium salts. These compounds were assayed as inhibitors of catechol O-methyltransferase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…After previous observation that the glycosidic portions of stevioside (78) and rebaudioside (82), linked to the C-19 position of the kaurane skeleton, are not involved in essential interactions with the receptors of the gustative cells, DuBois and collaborators [160,161] proposed the synthesis of analogous glycosides by substitution of the glycosidic portions for other groups with similar polarities, without the loss of the sweetening properties. As result, these researchers observed that the increase of the hydrophilic character of the group at C-19 caused the reduction of the bitter taste, which is characteristic of 78 and 82, leading to the synthesis of products that did not produce any such bitterness.…”
Section: Synthesis Of Kaurane Glycosidesmentioning
confidence: 99%
“…After previous observation that the glycosidic portions of stevioside (78) and rebaudioside (82), linked to the C-19 position of the kaurane skeleton, are not involved in essential interactions with the receptors of the gustative cells, DuBois and collaborators [160,161] proposed the synthesis of analogous glycosides by substitution of the glycosidic portions for other groups with similar polarities, without the loss of the sweetening properties. As result, these researchers observed that the increase of the hydrophilic character of the group at C-19 caused the reduction of the bitter taste, which is characteristic of 78 and 82, leading to the synthesis of products that did not produce any such bitterness.…”
Section: Synthesis Of Kaurane Glycosidesmentioning
confidence: 99%
“…The relative sweetness, evaluated by a professional human sensory panel [16], was nearly x 200 with respect to sucrose (stevioside is x 160). The quality of taste was also significantly improved, with a decrease of aftertaste and increase of deliciousness.…”
Section: 3)mentioning
confidence: 99%
“…Included among these stability studies on 1 were evaluations as dry powder, evaluations in model beverages and in buffers over a range of temperatures and pH values, and evaluations for photostability. In addition to our stability study work on 1, we have also (1) developed methods for purification, (2) conducted sensory studies, (3) identified impurities present in both the raw stevia leaf extract as well as in the purified material, (4) determined degradation pathways, and (5) carried out multiple preclinical and clinical safety assessment studies (4).…”
Section: Introductionmentioning
confidence: 99%